2020
DOI: 10.1177/0018720820922717
|View full text |Cite
|
Sign up to set email alerts
|

Curved Versus Flat Monitors: Interactive Effects of Display Curvature Radius and Display Size on Visual Search Performance and Visual Fatigue

Abstract: Objective The aim of this study is to examine the interactive effects of display curvature radius and display size on visual search accuracy, visual search speed, and visual fatigue. Background Although the advantages of curved displays have been reported, little is known about the interactive effects of display curvature radius and size. Method Twenty-seven individuals performed visual search tasks at a viewing distance of 50 cm using eight configurations involving four display curvature radii (400R, 600R, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The regression coefficient shows that the angle of view had the greatest influence on the blink frequency (0.507), followed by the viewing distance and the apparent height. Therefore, when studying the visual fatigue caused by electronic screens, the viewing angle, viewing distance, and visual height should be taken into account [33,34]. It can be seen from the verification experiment of the product that the visual fatigue of the subjects was delayed compared with the formal experiment, indicating that the construction of the regression model was effective.…”
Section: Discussionmentioning
confidence: 99%
“…The regression coefficient shows that the angle of view had the greatest influence on the blink frequency (0.507), followed by the viewing distance and the apparent height. Therefore, when studying the visual fatigue caused by electronic screens, the viewing angle, viewing distance, and visual height should be taken into account [33,34]. It can be seen from the verification experiment of the product that the visual fatigue of the subjects was delayed compared with the formal experiment, indicating that the construction of the regression model was effective.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, when the fifth article is satisfied, the pulse frequency r and tone intensity S are adjusted according to Eqs. ( 10) and (11).…”
Section: Lm-bpnn Improved By Bamentioning
confidence: 99%
“…Nutnicha et al [10] determined that humans increased their use of VDTs during COVID-19 lockdown periods. Kyung et al studied the effects of the curvature radii of VDT displays and the sizes of display screens on visual search accuracy and speed in addition to visual weariness [11]. The VDT operation mode of medical equipment is important because it affects the quality and development of medical instrumentation particularly for VDTs in laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…These studies in VR also concluded that user performance primarily depends on target widths and amplitudes. In addition, researchers showed that large curved displays offer many advantages over flat displays, as the user can be situated at a uniform distance from the center, offering higher levels of immersion and satisfaction [40,62]. However, there is limited research on pointing performance on curved displays as previous work on curved displays focuses mainly on viewing tasks [1,62,70] and reading tasks [40,54].…”
Section: Introductionmentioning
confidence: 99%